DNA Methyltransferase Inhibitor Promotes Human CD4+CD25hFOXP3+ Regulatory T Lymphocyte Induction under Suboptimal TCR Stimulation - Lu, Chun-Hao; Wu, Cheng-Jang; Chan, Cheng-Chi; Nguyen, Duc T.; Lin, Kuo-Ray; Lin, Syh-Jae; Chen, Li-Chen; Yen, Jeffrey Jong-Yong; Kuo, Ming-Ling (Frontiers in Immunology, 2016)
The "master transcription factor" FOXP3 regulates the differentiation, homeostasis, and suppressor function of CD4+ regulatory T (Treg) cells, which are critical in maintaining immune tolerance. Epigenetic regulation of FOXP3 expression has been demonstrated to be important to Treg cell development, but the induction of human Treg cells through epigenetic modification has not been clearly described. We report that the combination of the DNA methyltransferase inhibitor 5-azacytidine (5-Aza) and suboptimal T cell receptor (TCR) stimulation promoted CD4+CD25hFOXP3+ T cell induction from human CD4+CD25- T cells. 5-Aza treatment enhanced the expression of Treg cell signature genes, CD25, FOXP3, CTLA-4, and GITR, in CD4+CD25h cells. Moreover, 5-Aza-treated CD4+CD25h T cells showed potent suppressive activity in a cell contact-dependent manner and reduced methylation in the Treg-specific demethylated region (TSDR) in the FOXP3 gene. The analysis of cytokine production revealed that CD4+CD25- T cells with 5-Aza treatment produced comparable levels of interferon (IFN)-γ and transforming growth factor (TGF)-β, but less IL-10, and more IL-2 when compared to cells without 5-Aza treatment. The increased IL-2 was indispensible to the enhanced FOXP3 expression in 5-Aza-treated CD4+CD25h cells. Finally, 5-Aza-treated CD4+CD25h T cells could be expanded with IL-2 supplementation alone and maintained FOXP3 expression and suppressor function through the expansion. Our findings demonstrate that DNA demethylation can enhance the induction of human Treg cells and promise to solve one of the challenges with using Treg cells in therapeutic approaches.